Diagnóstico do sistema de abastecimento de água pela percepção do usuário na cidade de Pau dos Ferros/RN - Abrantes, Caio Guilherme Ferreira (Universidade Federal Rural do Semi-Árido, 2018)
Water is the natural resource responsible for maintaining the life of human beings and other living beings, supplying the existing chemical - biological needs, in which their lack entails several economic and social damages, as well as political disputes, for a variety of reasons. Therefore, it is of fundamental importance to preserve and conserve them to ensure the survival and development of cities, but to maintain the local supply is necessary that a continuous daily flow occurs. In this context, an exploratory and descriptive research was carried out in the city of Pau dos Ferros - RN, on the diagnosis of the Water Supply System - SAA based on the users' perception in the year 2018, in order to obtain besides the diagnostic characteristics of the place, volume of water and quantity of reservoirs, conducting system of water present in the residences. From the bibliographic study concerning the behavior of the state and the municipalities that compose it and with the aid of questionnaires containing selected questions to obtain a good diagnosis was applied to 367 residents in a random way, reaching 21 neighborhoods of the city of Pau dos Ferros for which at least 12 questionnaires per neighborhood were applied. In which it was possible to verify that the population is dissatisfied with the company responsible for CAERN water distribution, how does the system of rodizio created during the period of drought, which resulted in the collapse of the main reservoir of the city in the year 2016 as Souto (2017), some of the impacts generated by the local population, such as large periods without water supply and still provided an understanding of whether the water supply meets the requirements of pressure, quality and quantity, among others, such purposes. We can also verify some characteristics of the city, modifications in buildings with the construction of reservoirs with volumes over 5 thousand liters and how to live with water when reusing large portions of it, for example from laundry and shower, to washing, and irrigation, caused by the need caused by the lack of water resources for high periods and the quality of water for certain uses such as drinking and cooking food, where 47% of the population purchases mineral water.
Keywords: Crise hídrica; Satisfação; Rodízio; ENGENHARIAS::ENGENHARIA CIVIL